Tunable Microwave Conductance of Nanodomains in Ferroelectric PbZr0.2Ti0.8O3 Thin Film. (10th December 2021) - Burns, Stuart R.; Tselev, Alexander; Ievlev, Anton V.; Agar, Joshua C.; Martin, Lane W.; Kalinin, Sergei V.; Sando, Daniel; Maksymovych, Petro
Abstract: Ferroelectric materials exhibit spontaneous polarization that can be switched by electric field. Beyond traditional applications as nonvolatile capacitive elements, the interplay between polarization and electronic transport in ferroelectric thin films has enabled a path to neuromorphic device applications involving resistive switching. A fundamental challenge, however, is that finite electronic conductivity may introduce considerable power dissipation and perhaps destabilize ferroelectricity itself. Here, tunable microwave frequency electronic response of domain walls injected into ferroelectric lead zirconate titanate (PbZr0.2 Ti0.8 O3 ) on the level of a single nanodomain is revealed. Tunable microwave response is detected through first‐order reversal curve spectroscopy combined with scanning microwave impedance microscopy measurements taken near 3 GHz. Contributions of film interfaces to the measured AC conduction through subtractive milling, where the film exhibited improved conduction properties after removal of surface layers, are investigated. Using statistical analysis and finite element modeling, we inferred that the mechanism of tunable microwave conductance is the variable area of the domain wall in the switching volume. These observations open the possibilities for ferroelectric memristors or volatile resistive switches, localized to several tens of nanometers and operating according to well‐defined dynamics under an applied field. Abstract : Tunable microwave conductance is induced by ferroelectric switching in lead zirconate titanate (PbZr0.2 Ti0.8 O3 ). Through subtractive milling, statistical analysis, and finite element modeling, the mechanism of tunable microwave conductance as related to the domain wall density under the scanning probe is elucidated. The results are promising for ferroelectric memristors.